Legal Protection of Consumer in the Circulation of Food Products Containing Hazardous Ingredients - Salsabillah Ayu Puspita; Ida Kurnia (Jurnal Daulat Hukum, 2025)
This research aims to analyze the form of legal protection for consumer rights in the circulation of hazardous food products, using the case study of sodium dehydroacetate preservative use in Roti Okko products manufactured by PT Abadi Rasa Food. The entry of food products containing prohibited chemical substances has become a serious concern because it poses potential threats to public health and directly violates consumers’ rights to safety and security as stipulated in Article 4 of Law No. 8 of 1999 concerning Consumer Protection. This study employs a normative juridical method by examining relevant legislation, legal doctrines, literature, and official BPOM (Indonesian Food and Drug Authority) documents as primary data sources. The findings reveal that national regulations such as Law No. 18 of 2012 on Food, Law No. 36 of 2009 on Health, BPOM Regulation No. 22 of 2013, and Government Regulation No. 28 of 2004 provide a solid legal foundation for ensuring food safety, including the prohibition of hazardous food additives. However, recurring violations indicate weak enforcement and low compliance among business actors. The study also finds that BPOM holds the authority to withdraw products, revoke distribution licenses, and impose administrative sanctions. Therefore, the research concludes that the implementation of legal protection for consumers has not yet been optimal due to gaps in supervision mechanisms and the low awareness of business actors regarding food safety standards. The study recommends strengthening regulatory oversight, enhancing inter-agency coordination, and promoting continuous education for both business actors and consumers to achieve effective legal protection against the circulation of hazardous food products in Indonesia.